Enhancing Science Literacy in Secondary School Physics: A Systematic Review of Multimedia Integration Strategies and Resources - Burchard, Christer; Nguru, Festo; Pembe, Fortunata Kapacy (Scientia Publica Media, 2025)
Empirical research shows that multimedia can be used to enhance science literacy through developing high-level cognitive skills such as problem-solving, hypothesis testing, decision making, self-reflection, and critical and creative thinking among students. This is a systematic review that aimed at exploring the common instructional designs and resources used when integrating multimedia in secondary school physics teaching, to enhance science literacy. The review involved a critical search of relevant studies from three scientific databases, including Dimension, EBSCOHOST, and Scopus. Manual search was also involved in the study. The search was limited to research articles published between January 2020 and May 2024. 1121 publications were identified by literature search. 243 publications were screened, whereby 66 of them were sought for retrieval. 27 publications were assessed as eligible for the study. Finally, 7 publications were found most relevant for inclusion in the study. The review found out that the instructional designs employed include: integration of virtual laboratories with traditional demonstration methods; integration of PBL with e-learning tools; integration of inquiry-based instruction with virtual simulations; integration of traditional methods with simulations; and integration of traditional lab, virtual lab, and simulations. Apart from desktop computers and projectors which have been noted to have been included in the studies, also multimedia tools like virtual laboratories, simulation software, and interactive multimedia applications have been identified. Therefore, in order to enhance science literacy in physics teaching, multimedia needs to be integrated with actual practical works to bridge the gap between theory and practice. Additionally, integrating multimedia learning with innovative pedagogies such as project-based learning (PBL) and inquiry-based instruction is effective for developing science literacy. Finally, it is important to incorporate collaborative learning and discussions when teaching with multimedia.